Enhancing Kojic Acid Production in Aspergillus oryzae: Leveraging Crude Cellulase from Achatina fulica for Strain Improvement via Protoplasting and UV Mutagenesis - Putri Mulia, Ocha; Larosa, Febri LS; Septiarini, Tri Hastuti; Rahmasari, Ratika; Suryadi, Herman (Bogor Agricultural University, Indonesia, 2024)
This study aims to prove the ability of crude cellulase enzymes from snails for protoplasting Aspergillus oryzae cells and its application for strain improvement with UV mutagenesis. Snail enzyme was obtained from Achatina fulica by dissolving its digestion track and fractionating it with ammonium sulfate. The activity of fractions was measured Spectrophotometrically and used for cell protoplasting for 2 hours, then irradiated with UV for 10, 15, and 20 minutes, respectively, with 5 cm in the distance. Screening of mutants is carried out with 1% FeCl3, and the potential mutant strain was tested for kojic acid production in an aerobic state and determined by Spectrophotometry at 268 nm. The cellulase activity in crude snail enzyme was 11.5807 U/ml and increased to 16.3984 U/ml after fractionation. The best protoplast formation was obtained with a 60% fraction, which showed transparent performance under the microscope. The UV mutagenesis of protoplasts showed that the highest number of potential mutants was obtained from UV treatment for 15 minutes (41.67%). The potential mutants look dark brown (DBC), such as strain 10H3, and produced higher kojic acid concentration than the parent strain. In conclusion, UV mutagenesis of Aspergillus oryzae through protoplasting by crude cellulase of snail enzyme was effective and improved kojic acid concentration.